ISOLASI ASAM HUMAT DARI TANAH GAMBUT SUMATERA DAN KALIMANTAN DAN ANALISIS KANDUNGAN GUGUS FUNGSIONALNYA - Maya Rahmayanti; Erni Yunita; Masyithah Nisvi Prandini (Integrated Lab Journal, 2019)
Humic acid have done isolated from Peat soil of Sumatra and Kalimantan. The purpose of this research were to study the structure of hipotetik humic acid isolated from Sumatra and Kalimantan via FTIR spectrophotometry and analysis of functional groups through indirect titrationpotentiometric method. The FTIR spectra showed that the Sumatera and Kalimantan humic acid had the –COOH, -OH dan –NH groups. The results of titration showed that the value of the total acidity of humic acid isolated from Sumatra and Kalimantan were 710 and 570 cmol kg-1, respectively. The content of carboxyl functional groups were 260 and 300 cmol kg-1, respectively, and the contents of the phenolic hydroxyl group were 450 and275 cmol kg-1, respectively. The content of humic acid functional groups were included in the total acidity range structure of humic acid hypothetical according to Stevenson.